Faktor-faktor yang mempengaruhi corporate social responsibility dengan kinerja keuangan sebagai variabel moderasi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia - Siagian, Belinda Mora; Leon, Farah Margaretha; Purba, Yosephina Endang (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the factors that influence CSR with financial performance as a moderating variable in manufacturing companies listed on the IDX. The data used in this study is secondary data sourced from the annual reports and financial statements of manufacturing companies listed on the IDX during the 2015-2020 period. The research sample using purposive sampling method obtained a sample of 26 companies. The data analysis used is moderating regression analysis using Eviews 10. The results show that institutional ownership, managerial ownership and firm size have a positive and significant impact on CSR. Firm growth and debt ratio have no effect on CSR. Financial performance can moderate the direction of the positive relationship the influence of institutional ownership on CSR. Financial performance can moderate the direction of the negative relationship of managerial ownership on CSR. Financial performance cannot moderate the effect of firm growth on CSR. The results of this study provide information to management and investors where companies that have large institutional ownership can encourage CSR activities by paying attention to financial performance which can weaken the influence on CSR. Managerial ownership and large company size can encourage CSR activities by paying attention to financial performance which can strengthen the influence on CSR. In addition, improved financial performance and large institutional investors can encourage CSR activities. Declining financial performance and large managerial investors can also encourage CSR activities